The missing mass conundrum of post-common-envelope planetary nebulae. Issue Volume 14:Issue S343(2019) (August 2018) - Santander-García, Miguel; Jones, David; Alcolea, Javier; Wesson, Roger; Bujarrabal, Valentín
Abstract: Most planetary nebulae (PNe) show beautiful, axisymmetric morphologies despite their progenitor stars being essentially spherical. Angular momentum provided by a close binary companion is widely invoked as the main agent that would help eject an axisymmetric nebula, after a brief phase of engulfment of the secondary within the envelope of the Asymptotic Giant Branch (AGB) star, known as a common envelope (CE). The evolution on the AGB would thus be interrupted abruptly, its (still quite) massive envelope fully ejected to form the PN, which should be more massive than a PN coming from the same star were it single. We test this hypothesis by deriving the ionised+molecular masses of a pilot sample of post-CE PNe and comparing them to a regular PNe sample. We find the mass of post-CE PNe to be actually lower, on average, than their regular counterparts, raising some doubts on our understanding of these intriguing objects.